Contextual Interpretation: Correlation of KH Bisri Mustafa’s Interpretation and Abdullah Saeed’s Contextual Approach to Q.S. Yūsuf: 55 - As'ad Ar, Muhammad Syafi'i; Rahmatullah, M. Sultan Latif (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
Abstract.Interpretive works in the archipelago are often influenced by the subjectivity of mufassir. This can be seen from the language and script used in writing the interpretation, as well as the local issues included in the interpretation, one of which is the interpretation of Al-Ibrīz by K.H. Bisri Musthafa. The authorship of subjectivity in interpretation is inevitable, it is argued by Abdullah Saeed in his contextual approach that the first step that an interpreter must pay attention to is to understand the subjectivity of the mufassir. In his interpretation of Q.S Yūsuf: 55, K.H. Bisri Musthafa allows a person to ask for a position, but he also presents a hadith that forbids asking for office. To produce a contemporary meaning and become a solution to current social problems, the author will also read the verse through the contextual approach of Abdullah Saeed. This article aims to see how the interpretation of Q.S Yūsuf: 55 in the interpretation of Al-Ibrīz and also in the contextual approach of Abdullah Saeed. Then the author also wants to show the correlation between the results of the interpretation of the two. The method used in this study is descriptive-analytical, the results of which will expose the contextual correlation of the interpretation of KH. Bisri Musthafa and the results of interpretation through Saeed's contextual approach to Q.S Yūsuf: 55. The results of this study prove that the moral ideal of the verse is that a Muslim is required to participate in advancing the life of the nation and state while volunteering as a leader is one of the wasīlaḥ in achieving that goal.